2021
DOI: 10.7717/peerj-cs.516
|View full text |Cite
|
Sign up to set email alerts
|

VisTAS: blockchain-based visible and trusted remote authentication system

Abstract: The information security domain focuses on security needs at all levels in a computing environment in either the Internet of Things, Cloud Computing, Cloud of Things, or any other implementation. Data, devices, services, or applications and communication are required to be protected and provided by information security shields at all levels and in all working states. Remote authentication is required to perform different administrative operations in an information system, and Administrators have full access to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Moreover, some recent multi-factor authentication studies have presented new categorizations for each factor (Ali et al, 2021;Yazid et al, 2019;Liu et al, 2020) that are different from the traditional four factors emphasized in this paper; thus, these new, categorized factors can be overlapping in terms of the traditional categorization. Although the above studies have mentioned usability, the term is interpreted in different ways.…”
Section: Related Workmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, some recent multi-factor authentication studies have presented new categorizations for each factor (Ali et al, 2021;Yazid et al, 2019;Liu et al, 2020) that are different from the traditional four factors emphasized in this paper; thus, these new, categorized factors can be overlapping in terms of the traditional categorization. Although the above studies have mentioned usability, the term is interpreted in different ways.…”
Section: Related Workmentioning
confidence: 89%
“…Numerous multi-factor authentication schemes have been proposed so far, but it has been reported that real and practical implementation is little, since they require too much effort from the user with a security level not as expected (Wang et al, 2020). Also, using some unfriendly, high-tech factors may inhibit use of those schemes because it requires a high user skill level, and authentication devices are not available everywhere (Ali et al, 2021). This is in line with a study (Das et al, 2019) revealing that more userfriendly multi-factor authentication is relatively essential, though very few existing papers focus on user evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…Public blockchains are generally preferred in applications where the participation of cryptocurrencies or the entire society is expected. On the other hand, private blockchains [41] are frequently preferred in cases where privacy and access are desired to be limited. Blockchains, which are designed to be integrated into hospital systems, are the preferred models of the digital services offered by states to their citizens and are implemented with blockchain technology.…”
Section: Blockchain: An Overviewmentioning
confidence: 99%
“…Digitalization is one of the most promising tools for combating one of the world's most enduring challenges, corruption (Santiso, 2022). By incorporating IT into various government functions, the Philippines aims to create a more accessible and citizen-centric service (Ali et al, 2021).…”
Section: Introductionmentioning
confidence: 99%